The Financial-Accounting Audit in Pre-University Educational Institutions in Romania - Anișoara – Elena Pavelescu (Belbe) (Ovidius University Annals: Economic Sciences Series, 2022)
The purpose of the research is to identify the specific elements of the audit carried out in educational institutions in Romania. The objectives of the research are to offer some practical suggestions for carrying out an audit process in the school and to identify the steps followed in a financial-accounting audit mission. The audit carried out in pre-university education institutions in Romania aims to improve management, by providing assurance services, which represent objective examinations of evidence, establishing whether they operate economically, effectively and efficiently, to identify deficiencies and formulate recommendations for their correction.